The Effectiveness of STAD-Type Cooperative Learning Model Based on Online Media in Comprehending Physics Concepts - Juniar Rasyid; Eka Damayanti; Sudirman Sudirman; Rafiqah Rafiqah (STKIP Singkawang, 2023)
The concept comprehension of physics learning becomes the most important aspect that must be considered due to the conditions in the COVID-19 pandemic, the school implements online learning system that has potential to cause misconceptions among students. This research aims at finding out the effectiveness of STAD-type Cooperative Learning Model based on online media in comprehending physical concepts in class X MIA 1 SMAN 1 Tinambung. The research type is quasi-experiment that the data collection applied the concept comprehending test. The data were then analyzed using independent sample t-test. The results revealed that there was a difference in comprehending the concept among students who were taught using online media-based on the STAD-type in cooperative learning model with students who were taught using conventional learning based on online media. The results of effectiveness test conducted by comparing variance values showed that cooperative learning of STAD type effectively improved the concept comprehension. The findings in this study imply that the learning process during the Covid-19 pandemic can implement a media based on STAD-type cooperative learning model so that students still have appropriate comprehension of the learning material concept.